The Dynamics of Merariq Kodeq Implementation in Sasak Customary Traditions: A Phenomenological and Ethnographic Study - Siti Hartati Jenab; Nurin Rochayati; Arif Arif; Ravindra A. Jadhav (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The Merariq Kodeq tradition is one of the cultural heritages of the Sasak people that contains profound philosophical, moral, and social values. However, in its development, it faces various dynamics due to the influence of modernization and social change. The purpose of this study is to analyze the relationship between the subjective experiences of Merariq Kodeq practitioners through a phenomenological approach and the socio-cultural context of the Sasak people, which is studied ethnographically. This research uses qualitative methods with a phenomenological and ethnographic approach, conducted in Kuranji Village, Labuapi District, West Lombok Regency. Data collection methods included participatory observation, in-depth interviews, and document analysis, with informants comprising traditional leaders, religious leaders, village officials, community leaders, and adolescents. The results of the study show that Merariq Kodeq is not only understood as a traditional marriage practice, but also as a symbol of the collective identity of the Sasak people, representing the values of honor, politeness, and social solidarity. The implications of this study emphasize the importance of preserving local cultural values through educational, participatory, and collaborative approaches in order to maintain a balance between the preservation of customs and the dynamics of social change in the modern era.